Exploring the past to navigate the future: examining histories of higher dance education in China in an internationalized context. Issue 2 (4th May 2019) - Jin, Jin; Martin, Rose
ABSTRACT: China has a rich history of dance education and has established prominent tertiary dance institutions. Coupled with this is a growing global interest to engage with China, and connections are developing between Chinese and non-Chinese tertiary dance institutions. Within this curiosity and internationalization of dance education, there is the potential for authentic and exciting dialogue and exchange to occur. However, to allow such interactions to be the most beneficial it is of interest to look at the past of dance education in China to navigate the present and the future. Therefore, this article seeks to critically examine histories of higher dance education in China, to then provide critical understandings of higher dance education in China in the present and how these histories might inform future dance education. Within this article, there is a purposeful focus on the meanings of dance education in China, the relationship between politics and dance, and the examination-orientated education philosophies in teaching and learning dance within a Chinese context.